Effect of Amount of Guidance in Inquiry-Based Physics Laboratory on Conceptual Understanding and Metacognitive Awareness - Pesman, Haki; Ari, Uzeyir; Cirit, Didem Karakaya; Ayazgok, Buesra (Springer, 2025)
This study explores the influences of verification and guided inquiry-based physics laboratories on preservice science teachers' conceptual understanding of and misconceptions about simple electric circuits and their metacognitive awareness. In other words, the impact of the amount of guidance in inquiry teaching is being explored. There were two groups: (1) the experimental group, where the guided inquiry was implemented, and (2) the control group, where the verification style inquiry was implemented. The experiment was a true-experimental design because 55 pre-service science teachers were randomly assigned to the groups. This study used two pretest and posttest instruments: (1) Simple Electric Circuit Diagnostic Test (SECDT) with 11 items and (2) Metacognitive Awareness Inventory (MAI) with 52 items. The SECDT is a three-tier test to assess conceptual understanding and misconceptions of students about simple electric circuits, while the MAI assesses the metacognitive awareness of adults. The authors utilized a doubly multivariate repeated measures design, a multivariate test statistic for repeated measures, for analyzing the data. As a result, this study presents evidence of the positive effect of a guided inquiry-based physics laboratory concerning the verification-based one on preservice science teachers' conceptual understanding of simple electric circuits and their metacognitive awareness and presents conclusions based on the discussion.
Keywords: Science; Classroom